Study protocol for a multicenter phase II prospective externally controlled non-inferiority trial of hypofractionated re-irradiation in patients with recurrent high-grade glioma (RISinG) - A. M. de Jong; A. T. J. van der Boog; C. C. B. Post; F. Cialdella; D. B. P. Eekers; J. Hendrikse; M. C. A. Kramer; F. J. Lagerwaard; M. van der Meulen; M. E. P. Philippens; P. A. Robe; T. Rozema; et al. (PLoS ONE, 2026)
Background Reirradiation is a widely accepted option for second-line treatment in patients with recurrent glioma. However, no standard radiation regimen has been defined. Hypofractionation is aimed at reducing patients’ burden while maintaining the survival benefit, but may increase the risk of radionecrosis. The primary objective of this study is to determine if reirradiation in just 4 fractions is non-inferior to 10 fractions, regarding survival after reirradiation. Methods RISING trial A was an open label, randomized, non-inferiority, phase III trial with 1:1 allocation for 130 patients among all participating centers but failed to recruit according to planning. RISING trial B will be a phase II, multi-center, clinical trial with a historic control group. The experimental group receives 4 stereotactic fractions. The historic control group has received 10 fractions (standard-of-care) with a biologically equivalent dose on surrounding brain tissue. The primary endpoint is overall survival after reirradiation. The key secondary endpoint is progression-free survival. Other secondary endpoints are recurrence patterns, toxicity (specifically clinically relevant radionecrosis) and anti-edema treatment. We will collect and report on Health-Related Quality of Life (HRQoL) data in the experimental arm. Discussion We expect to demonstrate the non-inferiority and safety of a 4-fraction hypofractionation schedule for reirradiation of gliomas. This schedule may then become a standard-of-care option with minimal burden for patients with recurrent glioma, and limited use of scarce healthcare resources. Trial registration Registered at Netherlands Trial Register (NTR), Trial ID: NL72766.041.20, registered at 07-04-2020, https://www.onderzoekmetmensen.nl/en/trial/52643